PEMANFAATAN DATA NILAI JABATAN UNTUK PENYUSUNAN JALUR KARIR (STUDI KASUS DI POLMAN BANDUNG) - Achmad Muhammad (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
Many corporations put high efforts in improving its personnel welfare through a career management by which employees may forecast their career opportunities in the future. Despite implemented merit system, the available job value data gainedfrom job analysis and evaluation have yet to be optimally utilized for determining employees’ career path. This condition leads to weak work spirit and motivation on the part of the employees to provide their hardest efforts for the company due to unclear future career plan. Therefore, attempts need to be done to overcome the problem by using the available job value data for devising personnel career path. This may include two considerations, i.e. relative job value and cluster analysis result, which show proximity of factors and sub-factors among jobs having similarities. The result of this study is a proposition for a career path planfacilitating promotion or rotation from one job to another within or beyond a work unit. It can also be used as a base to post human resources on their right places.